2007
DOI: 10.3892/ijo.31.6.1309
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the serum response factor in hepatocellular carcinoma: Implications for epithelial-mesenchymal transition

Abstract: The acquisition of a migratory and invasive phenotype by cells of epithelial origin is associated with a gain of mesenchymal characteristics concomitant with a loss of the epithelial phenotype, a phenomenon referred to as epithelial-mesenchymal transition (EMT). Vimentin, a cytoplasmic intermediate filament, is characteristic of mesenchymal cells and is usually not expressed in epithelial cells. Increased expression of vimentin in carcinomas correlates with parameters of malignant potential such as tumor grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 29 publications
4
50
0
4
Order By: Relevance
“…The atypical expression of vimentin in epithelial cancer cells may be associated with local invasiveness and the potential for metastasis [41]. The aberrant overexpression of vimentin and its relation to tumor metastasis have been reported in HCC [42].…”
Section: Discussionmentioning
confidence: 99%
“…The atypical expression of vimentin in epithelial cancer cells may be associated with local invasiveness and the potential for metastasis [41]. The aberrant overexpression of vimentin and its relation to tumor metastasis have been reported in HCC [42].…”
Section: Discussionmentioning
confidence: 99%
“…6 Several studies have shown a correlation between human cancer and elevated levels of SRF or SRF binding to CArG boxes. [99][100][101][102] Whether such increases in SRF are causative or merely reflective of human cancer is unclear. Recently, however, the liver-restricted miR-122 was shown to be attenuated in human hepatocellular carcinomas where SRF levels are elevated.…”
Section: Srf and Cancermentioning
confidence: 99%
“…For immunohistochemical staining of tissue samples, the Dako Envision system, that uses dextran polymers conjugated with horseradish peroxidase (Dako, Carpinteria, CA, USA) was performed, as described previously (12). The sections were incubated for 2 h at room temperature with anti-SRF (1:100 dilution; Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Thyroid papillary carcinoma tissues were homogenized using an Ultra-Turrax homogenizer (Ika, Staufen, Germany) in ice-cold lysis buffer (50 mM Tris, pH 7.5, 150 mM NaCl, 0.5% Nonidet P-40) containing 1 mM phenylmethylsulfonyl fluoride, 2 μg/ml leupeptin, 2 μg/ml aprotinin, 5 mM sodium fluoride and 1 mM sodium orthovanadate. The lysates were subjected to Western blotting, as described previously (12). Since SRF is known to regulate expression of genes such as c-Fos, the expression levels of c-Fos and SRF protein were evaluated in an SRFtransfected cell line and thyroid papillary carcinoma tissues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation